Identifikasi Struktur Kebahasaan Judul Berita Media Daring Kompas.com pada Tataran Kategori Kata, Frasa, Klausa, dan Peran Semantis - Anggara, Adib; Kuswandi, Rendi; Yusuf, Muhammad Irfan; Kurniawan, Eva Dwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
News headlines are an important part of journalistic texts because they serve to convey the essence of information in a concise, clear, and attention-grabbing manner. This study aims to identify the linguistic structure of news headlines in the online media Kompas.com. This study uses a qualitative descriptive approach with 20 news headlines taken from Kompas.com as the object of study. Data collection techniques were carried out through documentation, while data analysis techniques were carried out by describing linguistic elements at the word, phrase, clause, and sentence levels. The analysis included word categories, phrase structures, semantic roles, and clause and sentence structures. The results show that Kompas.com news headlines are dominated by declarative sentences with complete and efficient structures, and tend to use nominal phrases and material verbs to convey the main events. In addition, the use of various semantic roles, such as actor, target, time, and place, was found to clarify the information in the news headlines. This linguistic structure reflects the characteristics of online journalistic language, which prioritises information events, language economy, and reader appeal.